BÚGINGI QARAQALPAQSTAN TELEJURNALISTIKASÍNDA MILLETLERARALIQLÍQ TATÍWLÍQTÍ ULLÍLAWSHÍ FILMLERDIŃ JARÍTÍLÍWÍ (ART AND CULTURE BULLETIN, 2024)
This article talks about the current state of Karakalpak television journalism.
Keywords: cinema; television; director; film; documentary film; feature film; production director; cameraman.